Manajemen Pelayanan Sebagai Upaya Peningkatan Penerimaan Pajak Progresif - Putu Adiani Ari Kurniawati (Jurnal Manajemen dan Bisnis, 2016)
The aim of this study was to understand the implemenation of service management in order toincrease the revenue of progressive tax at local revenue office and to find out the factor shatshould get attention in givig of service so aht the people satisfaction able to increase therevenue of progressive tax at local revenu office and to find out the factor that should getattention in giving of service, so that the people satisfcation able to reach. This study isqualitative. Source of data was primary and secondary data. Data collecting technique byobservation, interview, and documentation study. Data collectiong technique byinterpretative Weber methodology. The result shows implementation of service managementthat has been conducted to increase the revenue of progressive tax as follows: planning,organizing, actuating and controlling. Service optimalization process to improve the peoplesatisfaction. In order to increase the revenue of progresive tax by improve their servicemanagement by placing the people satisfaction at priority level and conduct repair on themedium and infrastructure improvemen by educating and training.Keywords: Service Management.